All the glory of Adam : liturgical anthropology in the Dead Sea scrolls - Fletcher-Louis, Crispin H. T. (Studies on the Texts of the Desert of Judah, 2002)
All the Glory of Adam examines Dead Sea Scroll texts which pertain to the Qumran community's understanding of (a) a transcendent, angelomorphic or divine humanity and (b) the role of cultic space and time, and the experience of worship, in the formation of such a humanity. The book contains twelve chapters. The first three are devoted to material which either antedates or provides important cognate material to the peculiarly sectarian material studied in the remaining chapters (esp. the Book of Noah and Sirach). Chapters 4-6 examine texts devoted to a divine humanity (4Q381, Hodayoth , 1Q/4QInstruction et cetera), the divine or angelic Moses (4Q374 andamp; 4Q377) and the heavenly human priesthood (1QSb, 4Q511, 4Q418 81, 4Q545, 4Q541, 4Q468b et cetera). The seventh chapter discusses the mystical and theophanic significance of the high priest's breastpiece at Qumran. Chapters 8-11 are a revisionist reading of the Songs of the Sabbath Sacrifice as a liturgy for a divine humanity and chapter 13 proposes a new interpretation of 1QM 10-17 in the same vein. Apart from all DSS scholars the book will be useful for anyone working on biblical anthropology, messianism and Christology, and temple or cultic theology.